Aspek Leksikal Sinonimi Pada Cerkak Newyork-Singapura-Jakarta Karya Pirngadi - Linguistika Manumanasa, Sindhu; Sumarlam (Sutasoma : Jurnal Sastra Jawa, 2024)
Literary works are works created with artistic or aesthetic purposes using language as a medium to convey ideas, stories and emotions. In cerkak, the use of synonyms can be an important part of the richness of the language used by the author. Synonymy can be in the form of words with words, words with phrases, phrases with phrases, and clauses with clauses. This research aims to find out the lexical aspects of synonymy in the New York-Singapore-Jakarta cerkak by Pirngadi published in Panjebar Semangat magazine No. 35, September 2, 2023. The main data in this research is written data, in the form of sentences or speech or dialog in which there is synonymy and its context. The data source is Pirngadi's Newyork-Singapore-Jakarta cerkak published in Panjebar Semangat magazine No. 35, September 2, 2023. The method used is the listening method with the basic techniques of reading and recording techniques and using the agih method to analyze the data. The results obtained in this study are lexical aspects of synonymy totaling ten (10) in the form of words, words-phrases, phrases-words, and phrases-phrases. The use of synonymy is intended so that readers do not get bored reading the same word or phrase repeatedly. The use of synonymy is intended so that readers do not get bored reading the same words or phrases repeatedly.